The flight home effect during the COVID-19 pandemic: Evidence from syndicated loans - Bampinas, Georgios; Blomkvist, Magnus; Demetriades, Elias; Politsidis, Panagiotis N. (Journal of Financial Stability, 2025)
This paper provides evidence of a flight home effect in the syndicated loan market during the COVID-19 pandemic, where lenders rebalance their loan portfolios towards domestic borrowers. Specifically, a one standard deviation increase in COVID exposure in the lenders’ home country is associated with a 4.1 percentage point decrease in lenders’ share of foreign loans. This home bias eases with the intensity of government restrictions during the pandemic and strengthens with expansionary monetary policy. We further pinpoint an operative supply-side mechanism, where smaller, less capitalized banks with a higher proportion of non-performing loans are more likely to rebalance towards domestic borrowers. Although different forms of asymmetric information exert a material – yet not uniform – effect on the lenders’ rebalancing decisions, the flight home effect emerges independently of the existence of these information asymmetries.